Institute of Metals Division - Oxidation-Nitrification of Chromium at 1000°C - A. U. Seybolt; D. H. Haman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1964)
The rate of oxidation of the lowest nitride of chromium, Cr2N, was measured to be equal to the rate of oxidation of chromium metal. It was found that, while the presence of Cr2N in chromium does not affect the oxidation mechanism, a long exposure at high temperature affects the morphology of Cr2N in chromium, causing a massive internal nitriding along chromium pain boundaries. Marker expen' -ments showed that the rate of oxidation of Cr2N layers on chromium is determined by the rate of chromium diffusion through Cr,03. The rate of formation of Cr2N is determined by diffusion rate of nitrogen through Cr2N. This rate at 1000°C is around thirty times faster than the rate of oxiahtion. Evidence is presented which suggests that nitrogen from the air reaches the chromium through the Cr2O9 by migration through pores or cracks rather than by a diffusive process. IT has long been recognized that, when chromium or alloys containing substantial amounts of chromium are oxidized in air, some chromium nitride (Cr2N) is formed under the oxide scale. Although the presence of this nitride layer has often been described, there appears to have been no systematic study of the role played by the nitride during the oxidation process. Indeed, there have been conflicting re-ports'92 on the kinetics of oxidation of chromium and chromium alloys in air and in oxygen. However, it is now well-established'-5 that the rate-controlling process during the parabolic oxidation of chromium to Cr2O3 is chromium-ion diffusion through Cr2O3. Because of the importance of chromium-containing alloys as oxidation-resistant materials, it seemed desirable to investigate the behavior of chromium during oxidation with and without the presence of chromium nitride. Since a semicontinuous Cr2N layer forms relatively early during the oxidation of chromium in the air, chromium atoms must either pass out of or through the Cr2N layer to become incorporated in the growing Cr2O3 scale. Therefore, it seemed desirable to examine the oxidation behavior of the pure nitride. MATERIALS AND EXPERIMENTAL PROCEDURE The chromium used in this investigation consisted of slices of an ingot made from "five-nine" iodide chromium which had been argon-atmosphere melted in a Y2O 3-stabilized ZrO2 crucible in an induction furnace. The only impurity of any significance was 625 ppm of 0, which was usually reduced to a microscopically invisible amount by hydrogen annealing at 1400°C. However, one sample of chromium was used with the as-cast oxygen level as explained below. The samples were used after abrading through 600 Sic paper and then washing in toluene and alcohol. Both nitriding and oxidation experiments were performed in a vertical tube furnace connected to a glass vacuum system. 'This system was equipped with pressure measuring instruments for the range of 10 p to 1 atm, and a cartesian-diver pressure-control device was used in conjunction with a needle valve to allow control of pressure in the range of about 10 to 760 mm. The nitrogen or hydrogen gas was purified by passing through hot copper chips at 600°C, anhydrous calcium sulfate (Drierite), and liquid nitrogen. Oxygen gas was dried through the Drierite column and a dry-ice trap (-78°C). Changes in specimen weight were followed by a Pyrex helix used in conjunction with a cathetometer which could reproducibly be read to +0.001 cm, yielding an accuracy of about +0.2 mg. The spring was maintained in the cool upper part of the furnace tube where the temperature did not rise above about 35°C. The nitride in equilibrium with metallic chro-